(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Dilated cardiomyopathy (DCM) is a pathological condition of the heart muscle tissue, in which the systolic function of the heart decreases, manifested by dilation of the left ventricle. In this disease, a decrease in myocardial contractility reduces the cardiac output (circulatory efficiency), which leads to systolic dysfunction and decompensation of pulmonary and systemic circulation. The number of people suffering from this disease is increasing in countries around the world, including in our republic, regardless of political and economic conditions. In recent years, cardiologists have become increasingly interested in non-coronary myocardial diseases among cardiovascular diseases, due to the increasing number of patients with dilated cardiomyopathy (DCMP), which causes premature disability and death of able-bodied people.